Informality, labor regulation, and the business cycle - Gustavo Leyva; Carlos Urrutia (Banco de México, 2018)
We analyze the joint impact of employment protection and informality on macroeconomic volatility and the propagation of shocks in emerging economies. For this, we propose a small open economy business cycle model with frictional labor markets, labor regulation, and an informal sector, modeled as self-employment. The model is calibrated to the Mexican economy, in particular to business cycle moments for employment and informality obtained from our own calculations with the ENOE survey for the period 2005-2016. We show that international interest rate shocks, which affect specifically job creation in the formal sector, are key to obtain a counter-cyclical informality rate. In our model both the economy without an informal sector and the economy with informality but a lower burden of labor regulation feature higher volatility in employment but smaller fluctuations in TFP and output.
Keywords: E24; E32; F44; J65; 330; informality; business cycle; small open economy; job creation; employment protection; international interest rate shocks